2013
DOI: 10.3390/brainsci3020923
|View full text |Cite
|
Sign up to set email alerts
|

Musical Expertise and Second Language Learning

Abstract: Increasing evidence suggests that musical expertise influences brain organization and brain functions. Moreover, results at the behavioral and neurophysiological levels reveal that musical expertise positively influences several aspects of speech processing, from auditory perception to speech production. In this review, we focus on the main results of the literature that led to the idea that musical expertise may benefit second language acquisition. We discuss several interpretations that may account for the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 121 publications
(177 reference statements)
7
56
2
2
Order By: Relevance
“…In addition, these results suggest that increased auditory sensitivity may be one of the driving forces behind enhanced phonemic perception in musicians. They are in line with previous work showing that musical expertise facilitates the perception and pronunciation of foreign linguistic sounds (Delogu, Lampis, & Belardinelli, ; Gottfried, ; Kühnis et al., ; Milovanov, Pietilä, Tervaniemi, & Esquef, ; Sadakata & Sekiyama, ; Slevc & Miyake, ) and possibly the learning of foreign languages (Chobert & Besson, ; Dittinger, Chobert, Ziegler, & Besson, ; Dittinger et al., ). Taken together, these results have potentially strong societal implications for education because fine perception of nonnative phoneme is an important first step in foreign language learning.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, these results suggest that increased auditory sensitivity may be one of the driving forces behind enhanced phonemic perception in musicians. They are in line with previous work showing that musical expertise facilitates the perception and pronunciation of foreign linguistic sounds (Delogu, Lampis, & Belardinelli, ; Gottfried, ; Kühnis et al., ; Milovanov, Pietilä, Tervaniemi, & Esquef, ; Sadakata & Sekiyama, ; Slevc & Miyake, ) and possibly the learning of foreign languages (Chobert & Besson, ; Dittinger, Chobert, Ziegler, & Besson, ; Dittinger et al., ). Taken together, these results have potentially strong societal implications for education because fine perception of nonnative phoneme is an important first step in foreign language learning.…”
Section: Discussionsupporting
confidence: 91%
“…It is not surprising that musical expertise facilitates speech perception, since music and speech are similar in several ways (Patel, 2010;Besson et al, 2011). For one thing, music and speech are both complex auditory signals based on similar acoustic parameters: both pitch and duration contribute to the melodic and rhythmic aspects of music and to the linguistic functions of speech (Chobert and Besson, 2013). In addition, music and speech processing both require attention, memory, and similar sensorimotor abilities.…”
Section: Tone Perception and Musical Abilitymentioning
confidence: 99%
“…Musical experience has been shown to have significant influence on lexical tone and speech perception due to the similar acoustic parameters, especially frequency and duration, shared between music and speech [1]. A significant number of studies have revealed that musical experience benefits the perception of non-native lexical tones for non-tonal language participants [11], [12].…”
Section: Effect Of Musical Experiencementioning
confidence: 99%
“…Linguistic and extra-linguistic factors have been found to influence second language (L2) learning [1]. One of the linguistic factors, the proximity between native language (L1) and L2 phonetic inventory, plays a key role in determining L2 word learning performance [2].…”
Section: Introductionmentioning
confidence: 99%